The Risk and Time Preferences of Young Truants and Their Parents - Emma Antrobus; Victoria Baranov; Deborah A. Cobb-Clark; Lorraine Mazerolle; Agnieszka Tymula (Institute of Labor Economics (IZA), 2017)
We use an incentivized experiment to measure the risk and time preferences of truant adolescents and their parents. We find that adolescent preferences do not predict school attendance and that a unique police-school partnership program targeting school absences was most effective in reducing the truancy of adolescents with relatively risk-averse parents.
Keywords: D81; J13; I29; 330; adolescent preferences; time preferences; risk preferences; RCT; truancy